ANALISIS KERJASAMA SECRETARIAT OF THE PACIFIC REGIONAL ENVIRONMENT PROGRAMME (SPREP) TERKAIT PERUBAHAN IKLIM - Renaldi Christian Hasahatan Siregar Siagian; Regina Princesa; Rudi Kogoya; Renalda Ester Angkouw; Retta Marito Tambunan (Kajian Asia Pasifik, 2020)
Abstract Climate Action or handling related to climate change is one of the important points of the 17 goals contained in the Sustainable Development Goals (SDGs). Climate change has recently become a serious problem in the international world, so it really needs deep attention from every country or region. As is the case in the Pacific Islands region, climate change is a threat that can disrupt sustainable development in this region, especially since there is an issue of rising sea levels which can drown the islands in it. With this climate change problem, one way that can be done is to take action or take action. Based on this background, an intergovernmental body called The Secretariat of the Pacific Regional Environment (SPREP) was formed to deal with problems regarding climate change in the Pacific Islands. The aim of SPREP itself is to promote cooperation in the Pacific region, provide assistance to protect and enhance the environment, and to ensure sustainable development for present and future generations. The framework used in this article is based on the theory of liberalism. Keywords: Pacific Island, SPREP, climate change Abstrak Climate Action atau penanganan terkait perubahan iklim merupakan salah satu poin penting dari 17 tujuan yang terdapat dalam Sustainable Development Goals (SDGs). Perubahan iklim akhir-akhir ini merupakan masalah yang cukup serius dalam dunia internasional, sehingga sangat dibutuhkan perhatian yang mendalam dari setiap negara ataupun kawasan. Seperti halnya yang terjadi di wilayah Kepulauan Pasifik, perubahan iklim merupakan suatu ancaman yang dapat mengganggu pembangunan berkelanjutan di wilayah ini, terlebih lagi adanya isu kenaikan air laut yang dapat menenggelamkan pulau-pulau didalamnya. Dengan adanya permasalahan perubahan iklim ini, salah satu cara yang dapat dilakukan yaitu melakukan pergerakan atau tindakan. Berdasarkan latar belakang tersebut, dibentuklah badan antar pemerintah yang dinamakan The Secretariat of the Pacific Regional Environment (SPREP) untuk menangani permasalahan mengenai perubahan iklim di Kepulauan Pasifik. Tujuan dari SPREP itu sendiri adalah untuk mempromosikan kerjasama di kawasan Pasifik, memberikan bantuan untuk melindungi dan meningkatkan lingkungan, serta untuk memastikan pembangunan berkelanjutan bagi generasi sekarang dan masa depan. Kerangka pemikiran yang digunakan dalam artikel ini didasarkan pada teori liberalisme. Kata kunci: Kepulauan Pasifik, SPREP, perubahan iklim